2022
DOI: 10.1002/hep.32470
|View full text |Cite
|
Sign up to set email alerts
|

A pan‐genotype hepatitis C virus viral vector vaccine generates T cells and neutralizing antibodies in mice

Abstract: Background and Aims A prophylactic vaccine targeting multiple HCV genotypes (gt) is urgently required to meet World Health Organization elimination targets. Neutralizing antibodies (nAbs) and CD4+ and CD8+ T cells are associated with spontaneous clearance of HCV, and each may contribute to protective immunity. However, current vaccine candidates generate either nAbs or T cells targeting genetically variable epitopes and have failed to show efficacy in human trials. We have previously shown that a simian adenov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In this study, we conducted case studies to evaluate the prediction capability of our stacked model TROLLOPE in practical real‐life situations and compared its performance with the top-five base-classifiers. Specifically, we collected six experimentally verified TCE-HCVs from two previous studies [ 84 ]. The criteria for HCV epitopes selection in this case study were as follows: 1) they have to be experimentally verified from published research papers, 2) only short peptides (8–11 amino acid residues) that are CD8+ T-cell specific epitopes will be considered (not B-cell specific or CD4+ T-cell epitopes), and 3) these TCE-HCVs should not be found in both the training and independent test datasets.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we conducted case studies to evaluate the prediction capability of our stacked model TROLLOPE in practical real‐life situations and compared its performance with the top-five base-classifiers. Specifically, we collected six experimentally verified TCE-HCVs from two previous studies [ 84 ]. The criteria for HCV epitopes selection in this case study were as follows: 1) they have to be experimentally verified from published research papers, 2) only short peptides (8–11 amino acid residues) that are CD8+ T-cell specific epitopes will be considered (not B-cell specific or CD4+ T-cell epitopes), and 3) these TCE-HCVs should not be found in both the training and independent test datasets.…”
Section: Resultsmentioning
confidence: 99%
“…This understanding of E1 and E2 structure will significantly help in the discovery of more effective vaccine and may be a novel therapeutic option [ 187 ]. Donnison et al recently attempted a bivalent viral vector vaccine in mice and found that it could induce both pangenotypic viral-specific B- and T-cell responses [ 188 ]. Moreover, Pihl et al described a whole inactivated cell-culture-derived HC vaccine that was capable of inducing potent neutralizing antibodies [ 189 ].…”
Section: Frontiers Of Hepatitis Vaccinesmentioning
confidence: 99%
“…[45] Recently, these two immunogens have been successfully encoded in a viral vector and assessed in mice, generating pan-genotypic T cells and antibodies. [46] Furthermore, much has been learned about neutralizing epitopes, structures of E2 have been solved, and structures of the E1/E2 heterodimer have recently been reported-together, these insights will provide further insight into how to fix HCV glycoprotein-based immunogens into conformation, exposing their most vulnerable points for neutralization. The expression of HCV envelope immunogens on virus like particles and scaffold nanoparticles is an approach currently being intensively explored, taking advantage of advances in structural and computational techniques alongside the study of neutralizing antibodies in people who spontaneously resolve HCV.…”
Section: The Hcv Vaccine Pipelinementioning
confidence: 99%
“…Moving forward, exciting new approaches are seeking to overcome genetic diversity and the limitations of previous approaches; this includes the use of modified E2 sequences with HVR deleted43,44 and conserved segment T cell immunogens expressed in viral vectors 45. Recently, these two immunogens have been successfully encoded in a viral vector and assessed in mice, generating pan‐genotypic T cells and antibodies 46. Furthermore, much has been learned about neutralizing epitopes, structures of E2 have been solved, and structures of the E1/E2 heterodimer have recently been reported—together, these insights will provide further insight into how to fix HCV glycoprotein‐based immunogens into conformation, exposing their most vulnerable points for neutralization.…”
Section: The Hcv Vaccine Pipelinementioning
confidence: 99%